Anterior cingulate cortex differently modulates frontoparietal functional connectivity between resting‐state and working memory tasks. Issue 7 (6th January 2020) - Di, Xin; Zhang, Heming; Biswal, Bharat B
Abstract: The brain frontoparietal regions and the functional communications between them are critical in supporting working memory and other executive functions. The functional connectivity between frontoparietal regions are modulated by working memory loads, and are shown to be modulated by a third brain region in resting‐state. However, it is largely unknown whether the third‐region modulations remain the same during working memory tasks or were largely modulated by task demands. In the current study, we collected functional MRI (fMRI) data when the subjects were performing n‐back tasks and in resting‐state. We first used a block‐designed localizer to define the frontoparietal regions that showed higher activations in the 2‐back than the 1‐back condition. Next, we performed physiophysiological interaction (PPI) analysis using left and right middle frontal gyrus (MFG) and superior parietal lobule (SPL) regions, respectively, in three continuous‐designed runs of resting‐state, 1‐back, and 2‐back conditions. No regions showed consistent modulatory interactions with the seed pairs in the three conditions. Instead, the anterior cingulate cortex (ACC) showed different modulatory interactions with the right MFG and SPL among the three conditions. While the increased activity of the ACC was associated with decreased functional coupling between the right MFG and SPL in resting‐state, it was associated with increased functional coupling in the 2‐back condition. The observed task modulations support the functional significance of the modulations of the ACC on frontoparietal connectivity.